Ostrich Eggs and Peacock Feathers: Sacred Objects as Cultural Exchange between Christianity and Islam - Nile Green (Al-Masaq, Vol. 18, No. 1, March 2006, 2006)
This article uses the wide dispersal of ostrich eggs and peacock feathers among the different cultural contexts of the Mediterranean - and beyond into the Indian Ocean world - to explore the nature and limits of cultural inheritance and exchange between Christianity and Islam. These avian materials previously possessed symbolic meaning and material value as early as the pre-dynastic period in Egypt, as well as amid the early cultures of Mesopotamia and Crete. The main early cultural associations of the eggs and feathers were with death/resurrection and kingship respectively, a symbolism that was passed on into early Christian and Muslim usage. Mercantile, religious and political links across the premodern Mediterranean meant that these items found parallel employment all around the Mediterranean littoral, and beyond it, in Arabia, South Asia and Africa. As an essay in the uses of material culture in mapping cultural exchange and charting the eclectic qualities of popular religiosity, the article provides a wide-ranging survey of the presence of these objects, from their visual appearance in Renaissance paintings to their hanging in the shrines of Indo-Muslim saints. A final section draws conclusions on the relationship between shared objects, cultural boundaries and the writing of history.